The future of ocean governance and capacity development : essays in honor of Elisabeth Mann Borgese (1918-2002) - Borgese, Elisabeth Mann; Werle, Dirk, 1956- (International Law E-Books Online, Collection 2018, ISBN: 9789004353329., 2018)
The International Ocean Institute-Canada has produced this collection of over 80 insightful essays on the future of ocean governance and capacity development. The book honors the work of Elisabeth Mann Borgese (1918-2002), preeminent ocean advocate and founder of the IOI. More than 90 leading experts explore future challenges and opportunities for ocean governance and capacity development. Major themes include the law of the sea, ocean sciences, integrated coastal and ocean management, fisheries and aquaculture, communication and negotiations, maritime safety and security, ocean energy, and maritime transportation. The essay collection is aimed at professionals, students and citizens alike - covering themes that parallel those in the annual Training Program of IOI-Canada. A leading member of the International Ocean Institute's network of centers and focal points worldwide, IOI-Canada was founded by Elisabeth Mann Borgese in 1979.